A Comparative Study to Find the Effectiveness of Core Muscles Activation Over Conventional Exercises In Subjects with Mechanical Low Back Pain: Life Sciences-Physiotherapy - Karran Yangma; Santosh Rajak; Trishna Saikia Baruah; Abhijit Dutta (International Journal of Life Science and Pharma Research, 2022)
Mechanical low back pain is the main common reason for referral to physiotherapy clinic, and a chief reason for people complains, and both men and women are equally reported to be affected by this condition. It is found that core stabilization exercises have got significant improvement when compared to conventional back care exercises in improving the function and in relieving pain. To see the effectiveness of core muscles activation over conventional exercises along with Interferential Therapy (IFT) in each group for the reduction of pain and to increase the range of motion and improve the disability in subjects with mechanical low back pain. This is an experimental study where pre and post design were used with 40 subjects with mechanical low back pain were taken considering the selection criteria and divided into two groups. 20 subjects in Group-A received Core muscles activation exercises and IFT with pre and post test analysis and 20 subjects in Group-B received Conventional exercises and IFT with pre and post test analysis. Visual Analogue Scale (VAS) for pain intensity, Revised Oswestry Disability Index (R-ODI) for the disability improvement and Goniometry for range of motion. Statistical analysis was done by using paired ‘t’ tests which showed significant improvement in reducing pain, improving the quality of life and increasing the ROM in Group-A as compared to Group-B but as p > 0.05 so it was non significant. It is concluded that subjects in Group-A who received Core muscles activation exercises are more effective as compared to Group-B who received Conventional exercises and it is found that IFT with core activation exercises is very effective in reducing pain, increasing the ROM and improving the disability.